Storage facilities, workspace and conservation and preparation services from the foundation of the Ethnographic Museum to this day - Grčević, Mihaela (Array, 2019)
The text provides an overview of the changes made inside the Museum in terms of the positioning of the permanent exhibition and the extension of storage facilities and workspace from the foundation of the Museum in 1919 to this day. The building in which the Ethnographic Museum is located is one of a few buildings in the city of Zagreb that has been built for a specific museological purpose. Nevertheless, from its inception, its structure and the interior design concept were inadequate for the performance of all the museum activities and hence repurposing and room extensions have been performed several times.